Who Pays? Comparing Cost Sharing Models for a Gold Open Access Publication Environment. Issue 8 (16th November 2020) - Bruns, Andre; Rimmert, Christine; Taubert, Niels
Abstract: The article analyzes possible financial effects of Gold Open Access based on article processing charges. It responds to the question whether different cost sharing models lead to the same or different financial burdens for research organizations. The distributional effects are calculated for five models. For the overwhelming majority of organizations, all models result in similar expenditures, but there are also organizations where the difference between most and least expensive model results in a considerable amount. Therefore, it is likely that cost sharing models will become an issue in the debate on how to shoulder a transformation toward Open Access.